Draining effects - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2003)
Biodrainage. Principles, experiences and applications IPTRID Knowledge Synthesis Report No. 6, 2002. 90 pp. ISBN 9251047804 US$ 16 Euro 14.80